The evolution of ultrasound in rheumatology - Kang, Taeyoung (SAGE Publications, 2012)
Musculoskeletal ultrasound is a powerful tool not only for evaluating joint and related structures but also for assessing disease activity. Ultrasound in rheumatology has rapidly evolved and been incorporated into routine clinical practice over the past decade. Moreover, technological development of equipment has made it more accessible for rheumatologists. We present a review of advances in ultrasound in rheumatology, focusing on major chronological developments.